Effective STL : 50 specific ways to improve your use of the standard template library - Meyers, Scott (Scott Douglas) (Addison-Wesley professional computing series., 2001)
& Ldquo;This is Effective C++ volume three & ndash; it & rsquo;s really that good. & rdquo; & ndash; Herb Sutter, independent consultant and secretary of the ISO/ANSI C++ standards committee & ldquo;There are very few books which all C++ programmers must have. Add Effective STL to that list. & rdquo; & ndash; Thomas Becker, Senior Software Engineer, Zephyr Associates, Inc., and columnist, C/C++ Users Journal C++ & rsquo;s Standard Template Library is revolutionary, but learning to use it well has always been a challenge. Until now. In this book, best-selling author Scott Meyers (Effective C++, and More Effective C++) reveals the critical rules of thumb employed by the experts & ndash; the things they almost always do or almost always avoid doing & ndash; to get the most out of the library. Other books describe what & rsquo;s in the STL. Effective STL shows you how to use it . Each of the book & rsquo;s 50 guidelines is backed by Meyers & rsquo; legendary analysis and incisive examples, so you & rsquo;ll learn not only what to do, but also when to do it & ndash; and why . Highlights of Effective STL include: Advice on choosing among standard STL containers (like vector and list), nonstandard STL containers (like hash_set and hash_map), and non-STL containers (like bitset). Techniques to maximize the efficiency of the STL and the programs that use it. Insights into the behavior of iterators, function objects, and allocators, including things you should not do. Guidance for the proper use of algorithms and member functions whose names are the same (e.g., find), but whose actions differ in subtle (but important) ways. Discussions of potential portability problems, including straightforward ways to avoid them. Like Meyers & rsquo; previous books, Effective STL is filled with proven wisdom that comes only from experience. Its clear, concise, penetrating style makes it an essential resource for every STL programmer.